Communicate persuasively through the PR-SR binomial in the organization of sustainable events: Una orientación innovadora hacia la Agenda 2030 para el Desarrollo Sostenible en la etapa de pospandemia, donde Barcelona es referencia mundial - Huerta Molinero, Ana María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Persuasive communication is vital for an event and the publicity that is generated in the Mass Media. The methodology used is sequential, where after a literature review, different case studies have been analized using secondary sources to verify the presence of the PR-RS binomial in the organization of sustainable events in Barcelona. Likewise, Persuasive communication can contribute to enhancing the sustainability and value of events, the brands involved such us the cities, where they are held. Barcelona can be a reference in this innovation, to also be applied to the rest of Spain and worldwide.